Clinical medicine : a textbook for medical students and doctors - Kumar, Parveen J. (Parveen June); Clark, Michael L (Edinburgh ; Philadelphia : W.B. Saunders, 1998)
This is much more than an introduction to medicine but with just enough detail not to overwhelm. Clinical Medicine effectively communicates the latest developments in many fast-changing areas
Infectious diseases, tropical medicine and sexually transmitted diseases -- Cell and molecular biology, genetic disorders and immunology -- Nutrition -- Gastroenterology -- Liver, biliary tract and pancreatic diseases -- Haematological disease -- Medical oncology -- Rheumatology and bone disease -- Renal disease -- Water, electrolytes and acid-base homeostasis -- Cardiovascular disease -- Respiratory disease -- Intensive care medicine -- Adverse drug reactions and poisoning -- Environmental medicine -- Endocrinology -- Diabetes mellitus and other disorders of metabolism -- Neurological disease -- Psychological medicine -- Dermatology
Includes bibliographical references and index
Keywords: Clinical medicine; Pathology; Medicine; Clinical Medicine